Ti(C, N)-Fe15Ni10Cr cermets as alternative hard materials: Influence of the processing route and composition on their microstructure and properties. Issue 16 (15th August 2021) - de Nicolás, M.; Besharatloo, H.; Pereira, L.; Müller-Grunz, A.; Bertalan, C.; Useldinger, R.; Llanes, L.; Gordo, E.
Abstract: Processing route is a determining factor that affects the properties of hard materials. Although processing routes are well defined for WC-Co hardmetals, a complete study is needed to understand the factors influencing the properties when alternative compositions are developed. In this investigation, Ti(C, N)-Fe15Ni10Cr cermets were produced following conventional powder metallurgy routes. Two types of milling – attritor and planetary, using different vessel/ball materials – and of sintering regimes – sinter-HIP and high-vacuum – were used to process the specimens and compare their final properties. Carbon content was also included in the study as experimental variable. Density, porosity, microstructure, mechanical and magnetic properties, and corrosion behaviour of the resulting cermets were determined by using a wide range of characterization techniques. Optimization of their production led to materials with a competitive hardness-toughness combination, comparable to those exhibited by plain WC-Co grades. Evaluation of corrosion confirmed the improved resistance when Cr is included as alloying element and also compared to cobalt, as well as the superior corrosion response of Ti(C, N) with respect to WC.